STUDI SOSIAL EKONOMI MASYARAKAT TERHADAP PEMANFAATAN SUMBER DAYA ALAM DI DESA MATANO: A Community Socio-Economic Study On The Use Of Natural Resources In Matano Village - Adrayanti Sabar; Chinty Agustiningrum; Makkarennu Makkarennu; Supratman Supratman (Jurusan Kehutanan -FHIL-UHO, 2023)
Matano Village which is near the conservation area, namely Lake Matano Nature Park and Faruhumpenai Nature Reserve is the background of this research to examine the social and economic conditions of the people in Matano Village from the perspective of how the community is able to fulfill their livelihood which is then explained in more detail through theory five main assets. The research was conducted in Matano Village, Nuha District, East Luwu Regency, South Sulawesi Province in June-August 2022. The method used in this research was purposive sampling. The data collected is in the form of primary data obtained through interviews with the community and secondary data obtained through literature relating to the socio-economic conditions of the community. The data analysis used in this study is a qualitative and quantitative description using the concept of livelihood assets, describing the four assets utilized by the people in Matano Village, and financial assets are calculated using the income, expenditure and saving formulas. The results showed that the community's main natural capital was the forest as a place for gardening and looking for non-timber forest products. The community's human capital is the expertise to make woven handicrafts from forest pandanus and palm trees. The community obtains their economic capital from their main livelihood, namely pepper farmers, side income is obtained from the sale of woven products. In marketing garden or handicraft products, people use networks, beliefs and groups as their social capital. Even so, the community has less physical capital, especially in road infrastructure and street lighting electricity.